The Crime of the Armenian Genocide from an International Law Perspective - Gea, Lenggo Anastasia Brilliant; Matakupan, Michelle Sharon Anastasia (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Genocide, or in Indonesian, Genosida, is a form of crime that attacks humanity by ruthlessly eliminating a group for the personal interests of the perpetrators themselves. Various acts of genocide include slaughtering a targeted group, which then physically and mentally assaults the victims. One example of genocide is the Armenian Genocide that occurred in the 20th century and lasted for 8 years. This action was focused on annihilating unarmed people, women, and children in Armenia according to the orders of the Ottoman Emperor at that time.